Small antenna efficiency by the reverberation chamber and the Wheeler Cap methods - Azremi, Abdullah Al Hadi; Ghafouri Shiraz, H.; Hall, Peter S. (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org